Polymer lithium ion battery for low-temperature discharge and preparation method thereof

By using a composite conductive agent composed of spinel lithium titanate microspheres, nano-silicon powder and expanded graphite, combined with polyacrylonitrile coating and cyclization treatment, the problem of poor discharge performance of polymer lithium batteries at low temperatures is solved, and a higher lithium ion transmission rate and conductivity is achieved, which significantly improves the low-temperature discharge performance and energy density of the battery.

CN119742464AActive Publication Date: 2025-04-01ROOFER ELECTRONICS TECH SHANWEI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411916439.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing polymer lithium batteries have poor discharge performance in low temperature environments, and graphite negative electrode materials are easy to stack, reducing the embedding and release of lithium ions.

Method used

The composite conductive agent is composed of spinel lithium titanate microspheres, nano-silicon powder and expanded graphite, combined with polyacrylonitrile coating and cyclization treatment to form a stable electrode material to improve the transmission rate and conductivity of lithium ions.

Benefits of technology

It significantly improves the discharge performance of polymer lithium-ion batteries at low temperatures, enhances the embedded and release capabilities of lithium ions, avoids the crushing of electrode materials at low temperatures, and improves the energy density and low temperature stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206924640000141
    Figure BDA0005206924640000141
  • Figure BDA0005206924640000151
    Figure BDA0005206924640000151
Patent Text Reader

Abstract

The invention relates to the technical field of low-temperature lithium ion batteries, and discloses a polymer lithium ion battery for low-temperature discharge and a preparation method thereof.The preparation method comprises the following preparation steps that lithium cobalt oxide, a polyvinylidene fluoride binder and carbon black are mixed and stirred to obtain positive electrode slurry, an aluminum foil current collector is coated with the positive electrode slurry, a roller press is used for rolling, and the polymer lithium ion battery for low-temperature discharge is obtained. Obtaining a positive plate; mixing and stirring the composite conductive agent, carboxymethyl cellulose and acrylic resin to obtain negative electrode slurry, coating a copper foil current collector with the negative electrode slurry, and rolling by using a roller press to obtain a negative plate; uniformly winding a layer of diaphragm on the surface of the negative plate, and then mutually winding with the positive plate to form a battery cell; and placing the cell in a PET heat shrink tube, injecting an electrolyte, sealing and curing to obtain the polymer lithium ion battery. And the negative plate formed by the composite conductive agent is beneficial for embedding lithium ions into expanded graphite layers, so that the lithium ion storage capacity is improved, and the discharge performance at low temperature is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low-temperature lithium-ion batteries, in particular to a polymer lithium-ion battery for low-temperature discharge and a preparation method thereof. Background Art

[0002] Compared with liquid lithium batteries, polymer lithium-ion batteries have many obvious advantages such as high energy density, smaller size, ultra-thinness, light weight and high safety. They are a new type of battery. In terms of shape, polymer lithium-ion batteries have ultra-thin characteristics and can be made into batteries of any shape and capacity according to product needs. Compared with liquid lithium-ion batteries, polymer lithium-ion batteries are not only safer, but also have the advantages of being thinner, with any area and any shape. The outer shell also uses a lighter aluminum-plastic composite film. However, the low-temperature discharge performance of existing polymer lithium batteries needs to be improved.

[0003] As a negative electrode material for lithium-ion batteries, graphite is conducive to the embedding and release of lithium ions at low temperatures and has good low-temperature discharge performance, which enables polymer lithium-ion batteries to have good discharge performance in low-temperature environments. However, the lamellar structure of graphite makes it easy for graphite negative electrode materials to stack, reducing the embedding and release of lithium ions and affecting the discharge performance of polymer lithium-ion batteries. Summary of the invention

[0004] The present invention provides a polymer lithium ion battery for low temperature discharge and a preparation method thereof, which solves the problems that the low temperature discharge performance of the polymer lithium battery is poor and graphite materials are easy to stack to reduce the embedding and release of lithium ions.

[0005] The technical solution of the present invention:

[0006] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0007] S1. The lithium cobalt oxide, polyvinylidene fluoride binder and carbon black are mixed and stirred to obtain a positive electrode slurry, the positive electrode slurry is coated on an aluminum foil current collector, and a roller press is used to roll to obtain a positive electrode sheet;

[0008] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin are mixed and stirred to obtain a negative electrode slurry, the negative electrode slurry is coated on a copper foil current collector, and a roller press is used to roll to obtain a negative electrode sheet;

[0009] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0010] S4. The battery cell is placed in a PET heat shrink tube, the electrolyte is injected, and after sealing, it is cured at 60-80°C for 2-3h to obtain a polymer lithium-ion battery;

[0011] The composite conductive agent is obtained by mixing polyethylene glycol fatty acid ester, expanded graphite and spinel lithium titanate microspheres;

[0012] The spinel lithium titanate microspheres are obtained by mixing nano silicon powder, a coupling agent, spinel lithium titanate and polyacrylonitrile, and then undergoing a cyclization treatment.

[0013] Furthermore, the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder, and carbon black is (8-10):(1.5-2):(3-5).

[0014] Furthermore, the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin is (6-9):(1.2-1.5):(3-3.5).

[0015] Furthermore, the aluminum foil current collector has a thickness of 10-20 μm and a purity of 99-99.5%.

[0016] Furthermore, the copper foil current collector has a thickness of 12-16 μm and a purity of 99-99.5%.

[0017] Furthermore, the diaphragm is a glass fiber diaphragm with a thickness of 9-12 μm.

[0018] Furthermore, the inner diameter of the PET (polyethylene terephthalate) heat shrink tube is 2-3 mm, and the outer diameter is 3-5 mm.

[0019] Furthermore, the electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of (1.6-2) g: (20-30) mL: (10-15) mL: (2-3) g: (2.5-3.5) g.

[0020] Further, the composite conductive agent is prepared by the following steps:

[0021] A1. Add spinel lithium titanate to deionized water and ethanol, stir evenly, add a coupling agent, stir until the reaction is complete, add nano-silicon powder and hydrochloric acid, continue stirring until the reaction is complete, filter, wash, and dry to obtain modified spinel lithium titanate;

[0022] A2. The modified spinel lithium titanate and polyacrylonitrile are added to dimethylformamide, stirred evenly, heated to 150-155 ° C, and after stirring, washed, dried, placed in a muffle furnace, heat treated at 200-230 ° C for 1-3h, and cooled to room temperature to obtain spinel lithium titanate microspheres;

[0023] A3. Add polyethylene glycol fatty acid ester and expanded graphite to deionized water, add spinel lithium titanate microspheres after ultrasonic treatment, continue ultrasonic treatment, heat to 90-110°C, stir, wash and dry to obtain a composite conductive agent.

[0024] Furthermore, during the above-mentioned reaction A1, the silanol groups produced by the hydrolysis of the coupling agent can be chemically bonded to the hydroxyl groups on the surface of the spinel lithium titanate, and the amino groups contained in the coupling agent can react with the amino groups on the surface of the nano-silicon powder, so that the nano-silicon powder is coated on the surface of the spinel lithium titanate.

[0025] Furthermore, in the above-mentioned A2 reaction process, the modified spinel lithium titanate is dispersed in polyacrylonitrile and dimethylformamide solvents, and the dimethylformamide is volatilized at 150-155°C, and then the polyacrylonitrile is coated on the surface of the modified spinel lithium titanate; after the polyacrylonitrile is coated on the surface of the modified spinel lithium titanate, it is heat-treated at 200°C, so that the nitrile group (-C≡N) in the polyacrylonitrile molecular chain interacts with the adjacent groups and is transformed into a stable ring structure, thereby obtaining spinel lithium titanate microspheres.

[0026] Furthermore, during the above-mentioned A3 reaction process, the polyethylene glycol fatty acid ester can enter the interlayer of the expanded graphite, expand the interlayer distance of the expanded graphite, and the hydroxyl groups carried on the polyethylene glycol fatty acid ester molecular chain can combine with the spinel lithium titanate microspheres, so that the spinel lithium titanate microspheres accompanied by the polyethylene glycol fatty acid ester can enter the interlayer of the expanded graphite to form a composite conductive agent.

[0027] Furthermore, in step A1, the ratio of spinel lithium titanate, deionized water, ethanol, coupling agent, nano-silicon powder and hydrochloric acid is (1-2) g: (15-25) mL: (45-55) mL: (0.3-0.6) g: (0.3-0.6) g: (0.1-0.3) mL.

[0028] Furthermore, in step A2, the amount ratio of the modified spinel lithium titanate, polyacrylonitrile and dimethylformamide is (2-3) g: (1-2) g: (25-35) mL.

[0029] Furthermore, in step A3, the ratio of the polyethylene glycol fatty acid ester, expanded graphite, deionized water, and spinel lithium titanate microspheres is (4-6) mL: (2-4) g: (80-120) mL: (1-1.4) g.

[0030] Furthermore, the coupling agent is γ-aminopropyltriethoxysilane.

[0031] Furthermore, the particle size of the expanded graphite is 1-3 μm.

[0032] Furthermore, the polyethylene glycol fatty acid ester is polyethylene glycol 400 monooleate.

[0033] Furthermore, the particle size of the spinel lithium titanate is 0.1-0.5 μm.

[0034] Furthermore, the particle size of the nano silicon powder is 30-40 nm.

[0035] Furthermore, the degree of polymerization of polyacrylonitrile is 15000-16000.

[0036] The present invention has the following beneficial effects:

[0037] (1) In the technical solution of the present invention, spinel lithium titanate has more lithium ion binding sites, which is conducive to the embedding and diffusion of lithium ions, and improves the charge and discharge performance of lithium ion batteries. Nano silicon powder is coated on the surface of spinel lithium titanate. On the one hand, nano silicon powder has a higher energy storage capacity, which can significantly improve the energy density of polymer lithium ion batteries and increase the low-temperature discharge performance of lithium ion batteries. The shape stability of nano silicon powder can avoid the volume expansion and contraction of expanded graphite during the charge and discharge process, which affects the performance of polymer lithium ion batteries. On the other hand, nano silicon powder is compounded with inorganic spinel lithium titanate, and the lithium storage capacity is stronger, which can significantly improve the discharge performance of the battery at low temperatures.

[0038] (2) In the technical scheme of the present invention, polyacrylonitrile is coated on the surface of modified spinel lithium titanate, and after cyclization, spinel lithium titanate microspheres are formed, which can improve the transmission rate of lithium ions, improve conductivity, and avoid the shedding of nano-silicon powder. After polyacrylonitrile is coated on the surface of modified spinel lithium titanate and subjected to cyclization treatment, the nitrile group (-C≡N) in the polyacrylonitrile molecular chain interacts with the adjacent groups and is transformed into a stable ring structure, which increases the rigidity, stability and elasticity of the molecule, can accommodate volume expansion, avoid the electrode material from being crushed at low temperature, and improve the discharge performance at low temperature.

[0039] (3) In the technical solution of the present invention, the expanded graphite has a porous structure and a high specific surface area, and there are a large number of micropores and channels inside it, which are conducive to the embedding and transmission of lithium-ion batteries; the spinel lithium titanate microspheres enter the expanded graphite interlayer along with the polyethylene glycol fatty acid ester to form a composite conductive agent. On the one hand, it can expand the distance between the expanded graphite layers, which is conducive to the embedding of lithium ions into the expanded graphite interlayers and improve the lithium ion storage capacity. On the other hand, the spinel lithium titanate microspheres can effectively shorten the diffusion path of lithium ions and effectively prevent the restacking of expanded graphite sheets, thereby maximizing the intercalation sites of lithium ions and improving the discharge performance at low temperatures.

[0040] (4) In the technical solution of the present invention, the epoxy group contained in the polypropylene glycol diglycidyl ether in the electrolyte can polymerize with the amino group of the polyetheramine to form a polymer electrolyte, and the polymer electrolyte does not contain residual initiator, which is beneficial to improving lithium ion conduction, can effectively reduce the internal resistance of the battery, and improve the discharge performance at low temperatures. DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.

[0043] Wherein, the coupling agent is γ-aminopropyltriethoxysilane.

[0044] The particle size of expanded graphite is 2.5 μm.

[0045] The polyethylene glycol fatty acid ester is polyethylene glycol 400 monooleate.

[0046] The particle size of spinel lithium titanate is 0.4 μm.

[0047] The particle size of nano silicon powder is 40nm.

[0048] The degree of polymerization of polyacrylonitrile is 15000.

[0049] The polyvinylidene fluoride binder was purchased from Shanghai Heyiyuan Plastic Raw Materials Co., Ltd.

[0050] Acrylic resin, CAS number 9003-01-4, purity 99%, was purchased from Zhengzhou Aikemu Chemical Co., Ltd.

[0051] Example 1

[0052] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0053] S1. Lithium cobalt oxide, polyvinylidene fluoride binder and carbon black were mixed and stirred at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, the positive electrode slurry was coated on an aluminum foil current collector, and a roller press was used to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black was 8:1.5:3; the rolling density was 2 g / cm 3 .

[0054] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 6:1.2:3; the rolling density was 1 g / cm 3 .

[0055] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0056] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 60°C for 2h to obtain a polymer lithium-ion battery.

[0057] The aluminum foil current collector has a thickness of 10 μm and a purity of 99%.

[0058] The copper foil current collector has a thickness of 12 μm and a purity of 99%.

[0059] The diaphragm is a glass fiber diaphragm with a thickness of 9 μm.

[0060] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 2mm and the outer diameter is 3mm.

[0061] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 1.6 g:20 mL:10 mL:2 g:2.5 g.

[0062] The composite conductive agent is prepared by the following steps:

[0063] A1. Add 1g of spinel lithium titanate to 15mL of deionized water and 45mL of ethanol, stir evenly, add 0.3g of γ-aminopropyltriethoxysilane, stir and react at 50°C for 10min, add 0.3g of nano-silicon powder and 0.1mL of 36% hydrochloric acid, continue stirring and reacting for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified spinel lithium titanate;

[0064] A2. 2 g of modified spinel lithium titanate and 1 g of polyacrylonitrile were added to 25 mL of dimethylformamide, stirred evenly, heated to 150 ° C, stirred until dimethylformamide volatilized, washed three times with deionized water, dried in an oven at 70 ° C for 10 min, placed in a muffle furnace, introduced argon at a rate of 1.5 L / min, heat treated at 200 ° C for 2 h, and cooled to room temperature to obtain spinel lithium titanate microspheres;

[0065] A3. Add 4 mL of polyethylene glycol 400 monooleate and 5 g of expanded graphite to 80 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1 g of spinel lithium titanate microspheres, continue ultrasonic treatment for 30 min, heat to 100 ° C, stir until the solvent evaporates, wash three times with deionized water, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0066] Example 2

[0067] A method for preparing a polymer lithium-ion battery for low-temperature discharge, comprising the following preparation steps: S1. mixing lithium cobalt oxide, polyvinylidene fluoride binder and carbon black, stirring at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, coating the positive electrode slurry on an aluminum foil current collector, and rolling using a roller press to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black is 9:1.8:4; the rolling density is 2.5 g / cm 3 .

[0068] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 8:1.3:3.3; the rolling density was 1.3 g / cm 3 .

[0069] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0070] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 70°C for 2.5h to obtain a polymer lithium-ion battery.

[0071] The aluminum foil current collector has a thickness of 15 μm and a purity of 99.3%.

[0072] The copper foil current collector has a thickness of 14 μm and a purity of 99.3%.

[0073] The diaphragm is a glass fiber diaphragm with a thickness of 10 μm.

[0074] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 2.5mm and the outer diameter is 4mm.

[0075] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 1.8 g:25 mL:13 mL:2.5 g:3 g.

[0076] The composite conductive agent is prepared by the following steps:

[0077] A1. Add 1.5 g of spinel lithium titanate to 20 mL of deionized water and 50 mL of ethanol, stir evenly, add 0.5 g of γ-aminopropyltriethoxysilane, stir and react at 50 ° C for 10 min, add 0.5 g of nano-silicon powder and 0.2 mL of 36% hydrochloric acid by mass, continue to stir and react for 10 min, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain modified spinel lithium titanate;

[0078] A2. 2.5 g of modified spinel lithium titanate and 1.5 g of polyacrylonitrile were added to 30 mL of dimethylformamide, stirred evenly, heated to 153 ° C, stirred until dimethylformamide volatilized, washed three times with deionized water, dried in an oven at 70 ° C for 10 min, placed in a muffle furnace, introduced argon at a rate of 1.5 L / min, heat treated at 220 ° C for 2 h, cooled to room temperature, and obtained spinel lithium titanate microspheres;

[0079] A3. Add 5 mL of polyethylene glycol 400 monooleate and 3 g of expanded graphite to 100 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1.2 g of spinel lithium titanate microspheres, continue ultrasonic treatment for 30 min, heat to 100 ° C, stir until the solvent evaporates, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0080] Example 3

[0081] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0082] S1. Lithium cobalt oxide, polyvinylidene fluoride binder and carbon black were mixed and stirred at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, the positive electrode slurry was coated on an aluminum foil current collector, and a roller press was used to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black was 10:2:5; the rolling density was 3 g / cm 3 .

[0083] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 9:1.5:3.5; the rolling density was 1.5 g / cm 3 .

[0084] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0085] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 80°C for 3h to obtain a polymer lithium-ion battery.

[0086] The aluminum foil current collector has a thickness of 20 μm and a purity of 99.5%.

[0087] The copper foil current collector has a thickness of 16 μm and a purity of 99.5%.

[0088] The diaphragm is a glass fiber diaphragm with a thickness of 12 μm.

[0089] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 3mm and the outer diameter is 5mm.

[0090] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 2g:30mL:15mL:3g:3.5g.

[0091] The composite conductive agent is prepared by the following steps:

[0092] A1. Add 2g of spinel lithium titanate to 25mL of deionized water and 55mL of ethanol, stir evenly, add 0.6g of γ-aminopropyltriethoxysilane, stir and react at 50°C for 10min, add 0.6g of nano-silicon powder and 0.3mL of 36% hydrochloric acid, continue stirring and reacting for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified spinel lithium titanate;

[0093] A2. 3 g of modified spinel lithium titanate and 2 g of polyacrylonitrile were added to 35 mL of dimethylformamide, stirred evenly, heated to 155 ° C, stirred until dimethylformamide volatilized, washed three times with deionized water, dried in an oven at 70 ° C for 10 min, placed in a muffle furnace, introduced argon at a rate of 1.5 L / min, heat treated at 230 ° C for 3 h, cooled to room temperature, and obtained spinel lithium titanate microspheres;

[0094] A3. Add 6 mL of polyethylene glycol 400 monooleate and 4 g of expanded graphite to 120 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1.4 g of spinel lithium titanate microspheres, continue ultrasonic treatment for 30 min, heat to 110 ° C and stir until the solvent evaporates, wash three times with deionized water, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0095] Comparative Example 1

[0096] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0097] S1. Lithium cobalt oxide, polyvinylidene fluoride binder and carbon black were mixed and stirred at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, the positive electrode slurry was coated on an aluminum foil current collector, and a roller press was used to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black was 10:2:5; the rolling density was 3 g / cm 3 .

[0098] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 9:1.5:3.5; the rolling density was 1.5 g / cm 3 .

[0099] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0100] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 80°C for 3h to obtain a polymer lithium-ion battery.

[0101] The aluminum foil current collector has a thickness of 20 μm and a purity of 99.5%.

[0102] The copper foil current collector has a thickness of 16 μm and a purity of 99.5%.

[0103] The diaphragm is a glass fiber diaphragm with a thickness of 12 μm.

[0104] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 3mm and the outer diameter is 5mm.

[0105] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 2g:30mL:15mL:3g:3.5g.

[0106] The composite conductive agent is prepared by the following steps:

[0107] A1. 3 g of spinel lithium titanate and 2 g of polyacrylonitrile were added to 35 mL of dimethylformamide, stirred evenly, heated to 155 ° C, stirred until dimethylformamide volatilized, washed three times with deionized water, dried in an oven at 70 ° C for 10 min, placed in a muffle furnace, introduced argon at a rate of 1.5 L / min, heat treated at 230 ° C for 3 h, and cooled to room temperature to obtain spinel lithium titanate microspheres;

[0108] A2. Add 6 mL of polyethylene glycol 400 monooleate and 4 g of expanded graphite to 120 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1.4 g of spinel lithium titanate microspheres, continue ultrasonic treatment for 30 min, heat to 110 ° C and stir until the solvent evaporates, wash three times with deionized water, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0109] Comparative Example 2

[0110] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0111] S1. Lithium cobalt oxide, polyvinylidene fluoride binder and carbon black were mixed and stirred at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, the positive electrode slurry was coated on an aluminum foil current collector, and a roller press was used to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black was 10:2:5; the rolling density was 3 g / cm 3 .

[0112] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 9:1.5:3.5; the rolling density was 1.5 g / cm 3 .

[0113] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0114] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 80°C for 3h to obtain a polymer lithium-ion battery.

[0115] The aluminum foil current collector has a thickness of 20 μm and a purity of 99.5%.

[0116] The copper foil current collector has a thickness of 16 μm and a purity of 99.5%.

[0117] The diaphragm is a glass fiber diaphragm with a thickness of 12 μm.

[0118] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 3mm and the outer diameter is 5mm.

[0119] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 2g:30mL:15mL:3g:3.5g.

[0120] The composite conductive agent is prepared by the following steps:

[0121] A1. Add 2g of spinel lithium titanate to 25mL of deionized water and 55mL of ethanol, stir evenly, add 0.6g of γ-aminopropyltriethoxysilane, stir and react at 50°C for 10min, add 0.6g of nano-silicon powder and 0.3mL of 36% hydrochloric acid, continue stirring and reacting for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified spinel lithium titanate;

[0122] A2. Add 6 mL of polyethylene glycol 400 monooleate and 4 g of expanded graphite to 120 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1.4 g of modified spinel lithium titanate, continue ultrasonic treatment for 30 min, heat to 110 ° C and stir until the solvent evaporates, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0123] Comparative Example 3

[0124] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0125] S1. Lithium cobalt oxide, polyvinylidene fluoride binder and carbon black were mixed and stirred at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, the positive electrode slurry was coated on an aluminum foil current collector, and a roller press was used to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black was 10:2:5; the rolling density was 3 g / cm 3 .

[0126] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 9:1.5:3.5; the rolling density was 1.5 g / cm 3 .

[0127] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0128] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 80°C for 3h to obtain a polymer lithium-ion battery.

[0129] The aluminum foil current collector has a thickness of 20 μm and a purity of 99.5%.

[0130] The copper foil current collector has a thickness of 16 μm and a purity of 99.5%.

[0131] The diaphragm is a glass fiber diaphragm with a thickness of 9-12μm.

[0132] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 3mm and the outer diameter is 5mm.

[0133] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 2g:30mL:15mL:3g:3.5g.

[0134] The composite conductive agent is prepared by the following steps:

[0135] A1. Add 2g of spinel lithium titanate to 25mL of deionized water and 55mL of ethanol, stir evenly, add 0.6g of γ-aminopropyltriethoxysilane, stir and react at 50°C for 10min, add 0.6g of nano-silicon powder and 0.3mL of 36% hydrochloric acid, continue stirring and reacting for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified spinel lithium titanate;

[0136] A2. 3 g of modified spinel lithium titanate and 2 g of polyacrylonitrile were added to 35 mL of dimethylformamide, stirred evenly, heated to 155 ° C, stirred until the dimethylformamide volatilized, washed three times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain spinel lithium titanate microspheres;

[0137] A3. Add 6 mL of polyethylene glycol 400 monooleate and 4 g of expanded graphite to 120 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1.4 g of spinel lithium titanate microspheres, continue ultrasonic treatment for 30 min, heat to 110 ° C and stir until the solvent evaporates, wash three times with deionized water, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0138] Comparative Example 4

[0139] A method for preparing a polymer lithium ion battery for low temperature discharge, comprising the following preparation steps:

[0140] S1. Lithium cobalt oxide, polyvinylidene fluoride binder and carbon black were mixed and stirred at a rate of 250 r / min for 40 min to obtain a positive electrode slurry, the positive electrode slurry was coated on an aluminum foil current collector, and a roller press was used to obtain a positive electrode sheet, wherein the mass ratio of lithium cobalt oxide, polyvinylidene fluoride binder and carbon black was 10:2:5; the rolling density was 3 g / cm 3 .

[0141] S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin were mixed and stirred at a rate of 250 r / min for 40 min to obtain a negative electrode slurry, the negative electrode slurry was coated on a copper foil current collector, and a roller press was used to obtain a negative electrode sheet, wherein the mass ratio of the composite conductive agent, carboxymethyl cellulose and acrylic resin was 9:1.5:3.5; the rolling density was 1.5 g / cm 3 .

[0142] S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell;

[0143] S4. Place the battery cell in a PET heat shrink tube, inject the electrolyte, seal it, and cure it at 80°C for 3h to obtain a polymer lithium-ion battery.

[0144] The aluminum foil current collector has a thickness of 20 μm and a purity of 99.5%.

[0145] The copper foil current collector has a thickness of 16 μm and a purity of 99.5%.

[0146] The diaphragm is a glass fiber diaphragm with a thickness of 9-12μm.

[0147] The inner diameter of PET (polyethylene terephthalate) heat shrink tubing is 3mm and the outer diameter is 5mm.

[0148] The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of 2g:30mL:15mL:3g:3.5g.

[0149] The composite conductive agent is prepared by the following steps:

[0150] A1. Add 2g of spinel lithium titanate to 25mL of deionized water and 55mL of ethanol, stir evenly, add 0.6g of γ-aminopropyltriethoxysilane, stir and react at 50°C for 10min, add 0.6g of nano-silicon powder and 0.3mL of 36% hydrochloric acid, continue stirring and reacting for 10min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10min to obtain modified spinel lithium titanate;

[0151] A2. 3 g of modified spinel lithium titanate and 2 g of polyacrylonitrile were added to 35 mL of dimethylformamide, stirred evenly, heated to 155 ° C, stirred until dimethylformamide volatilized, washed three times with deionized water, dried in an oven at 70 ° C for 10 min, placed in a muffle furnace, introduced argon at a rate of 1.5 L / min, heat treated at 230 ° C for 3 h, cooled to room temperature, and obtained spinel lithium titanate microspheres;

[0152] A3. Add 4 g of expanded graphite to 120 mL of deionized water, ultrasonically treat at 250 W, 40 kHz for 30 min, add 1.4 g of spinel lithium titanate microspheres, continue ultrasonic treatment for 30 min, heat to 110 ° C and stir until the solvent evaporates, wash three times with deionized water, and dry in an oven at 70 ° C for 10 min to obtain a composite conductive agent.

[0153] The performance of the polymer lithium-ion batteries after treatment in Examples 1-3 and Comparative Examples 1-4 is now tested.

[0154] The polymer lithium-ion battery is fully charged to 4.2V at 0.5C current at room temperature.

[0155] Low temperature discharge performance test: After the polymer lithium-ion battery is fully charged to 4.2V at room temperature with a current of 0.5C, the fully charged battery is placed in -20℃, -40℃, and -60℃ environments, and discharged to 3V at 0.5C. The charge and discharge cycle is repeated 500 times, and the capacity retention rate and discharge efficiency of the battery are recorded. See Table 1 below.

[0156] Table 1 Performance test of polymer lithium ion batteries after treatment in Examples 1-3 and Comparative Examples 1-6

[0157]

[0158]

[0159] It can be seen from the data in Table 1 that the polymer lithium ion batteries prepared in Examples 1-3 have good low-temperature discharge performance. In Comparative Example 1, the composite conductive agent prepared by replacing the modified spinel lithium titanate with spinel lithium titanate is used to produce a polymer lithium ion battery, and its low-temperature discharge performance decreases, proving that the coating of nano silicon powder on the surface of spinel lithium titanate increases the low-temperature discharge performance of the battery, and the shape stability of the nano silicon powder avoids the volume expansion and contraction of the expanded graphite during the charge and discharge process.

[0160] In Comparative Example 2, the spinel lithium titanate microspheres were replaced with a composite conductive agent prepared from modified spinel lithium titanate and used to produce polymer lithium-ion batteries. The low-temperature discharge performance of the battery decreased, proving that polyacrylonitrile is coated on the surface of modified spinel lithium titanate and, after cyclization, forms spinel lithium titanate microspheres, which can increase the transmission rate of lithium ions, improve conductivity, avoid the shedding of nano-silicon powder, and improve the discharge performance at low temperatures.

[0161] The composite conductive agent prepared by polyacrylonitrile without cyclization treatment in Comparative Example 3 is used to produce polymer lithium-ion batteries, and its low-temperature discharge performance decreases, indicating that after polyacrylonitrile is coated on the surface of modified spinel lithium titanate, it is subjected to cyclization treatment, and the nitrile group (-C≡N) in the polyacrylonitrile molecular chain interacts with the adjacent groups and is transformed into a stable ring structure, which increases the rigidity, stability and elasticity of the molecule, can accommodate volume expansion, avoid electrode material crushing at low temperature, and improve the discharge performance at low temperature.

[0162] In Comparative Example 4, the composite conductive agent prepared without adding polyethylene glycol 400 monooleate was used to produce a polymer lithium-ion battery, and its low-temperature discharge performance decreased, proving that the spinel lithium titanate microspheres enter the expanded graphite interlayer along with the polyethylene glycol fatty acid ester, which can expand the spacing between the expanded graphite interlayers and increase the lithium ion storage capacity. In addition, the spinel lithium titanate microspheres can effectively shorten the diffusion path of lithium ions and improve the discharge performance at low temperatures.

[0163] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0164] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a polymer lithium-ion battery for low-temperature discharge, characterized in that: The method comprises the following preparation steps: S1. The lithium cobalt oxide, polyvinylidene fluoride binder and carbon black are mixed and stirred to obtain a positive electrode slurry, the positive electrode slurry is coated on an aluminum foil current collector, and a roller press is used to roll to obtain a positive electrode sheet; S2. The composite conductive agent, carboxymethyl cellulose and acrylic resin are mixed and stirred to obtain a negative electrode slurry, the negative electrode slurry is coated on a copper foil current collector, and a roller press is used to roll to obtain a negative electrode sheet; S3. After a layer of separator is evenly wound on the surface of the negative electrode sheet, it is then wound with the positive electrode sheet to form a battery cell; S4. The battery cell is placed in a PET heat shrink tube, the electrolyte is injected, and after sealing, it is cured at 60-80°C for 2-3h to obtain a polymer lithium-ion battery; The composite conductive agent is obtained by mixing polyethylene glycol fatty acid ester, expanded graphite and spinel lithium titanate microspheres; The spinel lithium titanate microspheres are obtained by mixing nano silicon powder, a coupling agent, spinel lithium titanate and polyacrylonitrile, and then undergoing a cyclization treatment.

2. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 1, characterized in that: The composite conductive agent is prepared by the following steps: A1. Add spinel lithium titanate to deionized water and ethanol, stir evenly, add a coupling agent, stir until the reaction is complete, add nano-silicon powder and hydrochloric acid, continue stirring until the reaction is complete, filter, wash, and dry to obtain modified spinel lithium titanate; A2. The modified spinel lithium titanate and polyacrylonitrile are added to dimethylformamide, stirred evenly, heated to 150-155 ° C, and after stirring, washed, dried, placed in a muffle furnace, heat treated at 200-230 ° C for 1-3h, and cooled to room temperature to obtain spinel lithium titanate microspheres; A3. Add polyethylene glycol fatty acid ester and expanded graphite to deionized water, add spinel lithium titanate microspheres after ultrasonic treatment, continue ultrasonic treatment, heat to 90-110°C, stir, wash and dry to obtain a composite conductive agent.

3. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 2, characterized in that: In step A1, the ratio of spinel lithium titanate, deionized water, ethanol, coupling agent, nano silicon powder and hydrochloric acid is (1-2) g: (15-25) mL: (45-55) mL: (0.3-0.6) g: (0.3-0.6) g: (0.1-0.3) mL.

4. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 2, characterized in that: In step A2, the modified spinel lithium titanate, polyacrylonitrile and dimethylformamide are used in a ratio of (2-3) g: (1-2) g: (25-35) mL.

5. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 2, characterized in that: In step A3, the ratio of the polyethylene glycol fatty acid ester, expanded graphite, deionized water, and spinel lithium titanate microspheres is (4-6) mL: (2-4) g: (80-120) mL: (1-1.4) g.

6. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 1, characterized in that: The thickness of the aluminum foil current collector is 10-20 μm, and the purity is 99-99.5%; the thickness of the copper foil current collector is 12-16 μm, and the purity is 99-99.5%.

7. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 1, characterized in that: The diaphragm is a glass fiber diaphragm with a thickness of 9-12 μm; the inner diameter of the PET heat shrink tube is 2-3 mm and the outer diameter is 3-5 mm.

8. The method for preparing a polymer lithium-ion battery for low-temperature discharge according to claim 1, characterized in that: The electrolyte is prepared by mixing lithium hexafluorophosphate, ethyl methyl carbonate, vinylene carbonate, polypropylene glycol diglycidyl ether and polyether amine in a dosage ratio of (1.6-2) g: (20-30) mL: (10-15) mL: (2-3) g: (2.5-3.5) g.

9. A polymer lithium ion battery prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Lithium titanate composite material and preparation method thereof and lithium-ion battery

    CN105958021A

  • Lithium ion battery

    CN107482166A

  • A core-shell structure negative electrode material for a lithium ion battery and preparation method thereof

    CN109103438A

  • Method for carbon-coating a lithium-ion battery electrode active material

    WO2016058492A1